Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Section: xvii, 204 pages ; 25 cm
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles